PENYULUHAN TENTANG JENIS TERAPI DAN KONTROL ASMA BERPENGARUH TERHADAP KUALITAS HIDUP PASIEN ASMA BRONKIAL - Marlin Sutrisna; Hanifah Hanifah; Neni Triana; Fatimah Nuraini Sasmita; Elsi Rahmadani (COVIT (Community Service of Health), 2022)
The quality of life of asthma patients is influenced by many factors, including the type of therapy and asthma control. The purpose of this community service is to provide insight and knowledge for the community/hospital visitors about the quality of life of asthma patients. The method used is a question-and-answer lecture/discussion and the provision of leaflets. The results obtained by the respondents' knowledge increased from before being given counseling to after being given counseling. The conclusion is that giving counseling increases the respondents' knowledge about types of therapy, asthma control, and the quality of life of bronchial asthma patients. It is hoped that by doing this community service, the community will share information with others about improving the quality of life Keywords: Type of Therapy, Asthma Control, Quality of Life, Counseling